HOW STANDARDS (SUCH AS XML) ACCOMPLISH ELECTRONIC AUTHENTICATION IN WEB SERVICES - Dana van der Merwe (Obiter, 2022)
Paper documents and “wet” signatures (made with ink) have given way to electronic data messages. This has led to problems with regard to the authentication of electronic “documents”. The present article explores some solutions in the shape of standards, eXtended Markup Language (XML) as a standardised format for data and the distinction between the (modern) Protocol and (traditional) Paper points of view in this regard.